Long-Term Burden of Higher Body Mass Index and Adult Arterial Stiffness Are Linked Predominantly Through Elevated Blood Pressure. Issue 1 (January 2019) - Liu, Yang; Yan, Yinkun; Yang, Xiangjun; Li, Shengxu; Bazzano, Lydia; He, Jiang; Chen, Wei
Abstract : Obesity and hypertension are important risk factors of arterial stiffness. However, the complex relationship between increased body mass index (BMI), elevated blood pressure (BP), and arterial stiffness is largely unknown. We aim to examine the mediation effect of elevated BP on the association of early life BMI, long-term burden, and trend of BMI with arterial stiffness in midlife. The longitudinal study cohort consisted of 1190 participants (829 whites and 361 blacks, 518 males, mean age=40.0 years at follow-up) who had been examined for BMI and BP 4 to 15 times from childhood and aortic-femoral pulse wave velocity (afPWV) in adulthood, with a mean follow-up period of 30.3 years. Total area under the curve (AUCt ) and incremental AUC (AUCi ) were calculated in random-effects models and used as long-term measures of BMI and BP. Total effects of BMI measures on adult afPWV, adjusted for covariates were all significant without adult BMI and systolic BP (SBP) measures included in the models. The mediation effects of adult SBP (20.2%) and SBP AUCi (16.9%) were significant on the childhood BMI-afPWV association. Adult SBP showed significant mediation effects of 36.7% on the BMI AUCi -afPWV association and 36.4% on the BMI AUCt -afPWV association. The mediation effect of SBP AUCi was estimated at 63.3% ( P <0.01) on the BMI AUCi -afPWV association. Diastolic BP had similar total and mediation effects. These findings suggest that the association of increased childhood BMI and its cumulative burden with adult arterial stiffness measured as afPWV is predominantly mediated through the long-term and increasing trend of BP. Abstract : Supplemental Digital Content is available in the text.